Cgrp Uptake into Perivascular Capsaicin-Sensitive Nerve Terminals - A. Sams-Nielsen; C. Orskov; I. Jansen-Olesen (The Scientific World Journal)
Specific mechanisms, providing reuptake of cathecholamine and amino acid neurotransmitters (e.g., serotonin and glutamate) into cells of the central nervous system are well known, whereas neuronal uptake of neuropeptides have not previously been reported.